Effects of Sm modification on biochar supported Mn oxide catalysts for low-temperature NH3-SCR of NO. (October 2021) - Chen, Lin; Yang, Jie; Ren, Shan; Chen, Zhichao; Zhou, Yuhan; Liu, Weizao
Abstract: In this study, Samarium (Sm) modification over Mn oxide biochar (BC)-based catalysts was synthesized and the activity of low-temperature selective catalytic reduction with NH3 (LT NH3 -SCR) of NO was measured. Varies in surface area and pore volume, structure, morphology, and surface chemistry of Sm-modified Mn/BC catalyst were investigated to analyze the effect of Sm on the physiochemical properties on catalyst. The Sm(0.2)-Mn/BC catalyst showed the highest NH3 -SCR activity with the NO conversion of 85% at 200 °C and best N2 selectivity in a broad temperature range of 75–250 °C. Doping with Sm species, Mn 4+ + Mn 3+ /Mn n+ and Oα /Oβ increased greatly, and the surface adsorbed oxygen were enhanced in Sm(0.2)-Mn/BC catalyst, which could promote the oxidation of NO, the NO conversion and N2 selectivity. In addition, weak and medium acid increased markedly after the Sm species added on catalysts, causing more active sites for SCR reaction. The NH3 -SCR reaction of Sm(0.2)-Mn/BC catalyst followed the L-H mechanism, and the generation of intermediate –NH2, NH4 + species and the N x O y species were observed which played vital part in the LT NH3 -SCR reaction. Highlights: Sm doping resulted in more active sites for SCR reaction. Sm-modification could promote the oxidation of NO. Sm-modification could increase both the De-NO x rate and the N2 selectivity. The NH3 -SCR reaction followed the L-H mechanism.